RANGE OF MOTION INDICATORS IN THE MAJOR BODY JOINTS DURING THE EXECUTION OF THE FORWARD JUMP TECHNIQUE WITH THE LEFT LEG IN BOXERS - F.Qo‘chqorov (Research Focus International Scientific Journal, 2025)
This article presents a kinematic analysis of the implementation of the left-foot stepping technique in boxing, and the movement of the body joints and the stepping trajectory in this process. As a result of this analysis, the necessary instructions and recommendations will be developed for improving the stepping technique of boxers.